Quantum dynamics of non-linear optomechanical systems - Abbs, Charlotte (2014)
This thesis explores the dynamics of optomechanical systems, which use radiation pressure to couple together optical and mechanical modes. Such systems display dynamics ranging from the quantum to the classical, with a variety of applications including ground state cooling and precision measurements. In this thesis two different geometries are presented for such a system in the form of the ‘reflective’ and ‘dispersive’ systems. Different aspects of the dynamics are investigated numerically and analytically.